Structural and charge density distribution studies on Tin Oxide nanoparticles for Supercapacitor application. (April 2020) - Murugan, A.; Siva, V.; Shameem, A.; Bahadur, S. Asath; Sasikumar, S.; Nallamuthu, N.
Highlights: SnO and Mn: SnO NPs synthesized via hydrothermal method. From XRD diffraction pattern calculated charge densities and chemical bond properties of the unit cell of both NPs were examined by Maximum Entropy Method. Electrochemical performance has been studied and obtained maximum specific capacitance of 246 F g -1 at a scan rate of 5 mV s -1 . In GCD of Mn:SnO working electrode retention of 107.92% from its first cycle without any decrement until over 1000 cycles. Abstract: Pure SnO and Mn doped SnO (Mn:SnO) nanoparticles have been successfully prepared by simplest route of the hydrothermal method. Prepared nanoparticles have been characterized by various analyses to understand structural, optical, morphological, elemental composition, Photoluminescence and electrochemical behaviours. The powder X-ray diffraction pattern analysis confirms the formation of crystalline nature of pure and Mn:SnO and its tetragonal structure. Functional group and elemental composition of prepared nanoparticles are confirmed using FTIR and EDX. The electrochemical performances of the prepared materials as working electrodes are analyzed by electrochemical workstation, analyzed parameters such as cyclic voltammetry and galvanostatic charge-discharge. From this study, maximum specific capacitance (Csp ) is 246.5 F g − 1 at 5 mA cm −2 is obtained. The optical energy band gap is found to be 3.17 and 2.61 eV for SnO and Mn:SnO nanoparticles, respectively. Graphical abstract: Image, graphical abstract